Інтеграція бібліотечних інформаційно-пошукових систем в аспекті уніфікації засобів лінгвістичного забезпечення - Кириленко, Олександр (Видавництво Львівської політехніки, 2018)
The role of unifying the linguistic support means in the integration of library information search systems is defined. The directions and the ways of improving the search capabilities of library information search systems in the context of their integration are presented.
Keywords: інформаційно-пошукові системи; бібліотечні інформаційно-пошукові системи; лінгвістичне забезпечення; авторитетний контроль